Adopsi Artificial Intelligence pada UMKM: Tinjauan Sistematis - Rizky Arya Pratama; Antonius Wahyu Sudrajat (MDP Student Conference, 2026)
This study examines research trends, adoption determinants, and the impact of Artificial Intelligence (AI) on Micro, Small, and Medium Enterprises (MSMEs) through a Systematic Literature Review (SLR). The review was conducted using the Kitchenham and Charters methodology and the PRISMA 2020 protocol to ensure methodological rigor and transparency. A total of 30 peer-reviewed journal articles published between 2020 and 2025 were selected from reputable international and national databases. The results indicate that the Technology–Organization–Environment (TOE) framework is the most dominant theoretical model used to explain AI adoption in MSMEs. Technological characteristics, organizational readiness, and environmental pressure are consistently identified as key determinants influencing adoption decisions. Furthermore, empirical evidence shows that AI adoption positively affects marketing performance, operational efficiency, innovation capability, and financial performance of MSMEs. Despite these benefits, empirical studies focusing on Indonesian MSMEs at the local level remain limited. Therefore, this study proposes a conceptual TOE–AI Adoption–MSME Performance model as a foundation for future empirical research.